2010
DOI: 10.3109/13651501003717243
|View full text |Cite
|
Sign up to set email alerts
|

Implementing electronic medical records in a psychiatric hospital: A qualitative study

Abstract: The objective of this study is to examine health care professionals' opinions of the critical events (opportunities and barriers) surrounding EMR implementation in a French teaching psychiatric hospital. This qualitative study was based on semi-structured interviews with 115 health care professionals: 16 psychiatrists, 84 nurses, six psychologists or social assistants and nine secretaries or administrative professionals. Interviews were thematically analysed. Most responders (96%) used EMR. Among these EMR use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 14 publications
1
51
0
1
Order By: Relevance
“…These findings are encouraging and suggest that implementing EHRs in mental health settings may be less different than doing so in other clinical environments than previously thought. On the contrary, several studies found that mental health nurses felt that there were a number of deficiencies in their experience using the EHR (Ammenwerth et al, 2001;Baillie et al, 2012;Boyer et al, 2010;Edwards et al, 2011;Saloman et al, 2010;Stahl, Granlund, GareAndersson, & Enskar, 2011). A summary of the findings of the literature review is detailed below.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings are encouraging and suggest that implementing EHRs in mental health settings may be less different than doing so in other clinical environments than previously thought. On the contrary, several studies found that mental health nurses felt that there were a number of deficiencies in their experience using the EHR (Ammenwerth et al, 2001;Baillie et al, 2012;Boyer et al, 2010;Edwards et al, 2011;Saloman et al, 2010;Stahl, Granlund, GareAndersson, & Enskar, 2011). A summary of the findings of the literature review is detailed below.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies reported that nurses experienced a number of immediate benefits of the EHR once implemented (Ammenwerth et al, 2001;Baillie, Chadwick, Mann, & Brooke-Read, 2012;Boyer, Samuelian, Fieschi, & Lancon, 2010;Edwards, Chiweda, Oyinka, McKay, & Wiles, 2011). These findings are encouraging and suggest that implementing EHRs in mental health settings may be less different than doing so in other clinical environments than previously thought.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Complexity of developing DOI reference number: 10.18293/SEKE2016-064 these software systems is well-known in the literature for many reasons, including heterogeneity of data and issues with interoperability between legacy systems [1], and design and architecture problems [2]. In addition, health applications are sensitive to important non-functional requirements, such as performance, security and safety of data [3] [4]. Therefore, developing and managing health information systems is a hard task.…”
Section: Introductionmentioning
confidence: 99%
“…In the application OpenSDE, authors have expanded the traditional row modeling methodology with additional columns to allow structured representation of medical narrative (Los, 2004). In the EHRs system context, Electronic Medical Records (EMRs) are currently being implemented in psychiatric hospitals throughout Europe (Boyer, et al, 2009a;Boyer, et al, 2009b;Boyer, et al, 2011). Taking a look at the international scenario, it can be determined that EHRs are not equally adopted in all countries.…”
Section: Introductionmentioning
confidence: 99%